The Image of Pura Geger and Its Surroundings in Gita Rasmi Sancaya: A Tourism Literature Study - Ni Luh Putu Aryasi Antari; I Nyoman Darma Putra; Luh Putu Puspawati (Green Publisher Indonesia, 2025)
This study examines the depiction of the Pura Geger temple and its surrounding areas as a tourist destination, as well as the portrayal of Dang Hyang Nirartha's role as a writer in the Geguritan Rasmi Sancaya. The temple holds significant potential to be developed as a tourist destination, and this research aims to explore how these places are represented in the literary text. Data were collected using qualitative methods, including observation, interviews, and literature study, and were presented descriptively. The study focuses on the literary portrayal of various locations mentioned in Geguritan Rasmi Sancaya, particularly those visited by Dang Hyang Nirartha. The research aims to identify and compare the textual and contextual descriptions of these sites, such as Gunung Payung, Pura Geger, Pura Bias Tugel, and Waterblow Nusa Dua. The findings reveal how these locations are depicted in the text and how this depiction contributes to the understanding of cultural and historical contexts of the area. The implications of this study suggest that literature, particularly Geguritan Rasmi Sancaya, can serve as an important tool for promoting the cultural significance of tourist destinations, offering insights into their historical value while encouraging tourism development.